Right ventricular size and function under riociguat in pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension (the RIVER study) - Marra, Alberto M.; Benjamin, Nicola; Eichstaedt, Christina; Egenlauf, Benjamin; Harutyunova, Satenik; Fischer, Christine; Grünig, Ekkehard (Respiratory research, 2018)
Riociguat is a soluble guanylate cyclase stimulator approved for pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTPEH). The objective of this study was to evaluate right heart size and function assessed by echocardiography during long term treatment with riociguat.